Strategies for the Afterlife in Eighteenth-Century Malta - Ciappara, Frans (Studies in church history, 2009)
According to Protestant eschatology, the dead are no longer with us. In the forceful words of Eamon Duffy they are ‘gone beyond the reach of human contact, even of human prayer’. But if this was the most devastating change in the mind of Protestants, Catholics affirmed Tridentine teaching on the cult of the dead by an ‘obsessional multiplication’ of suffrages or intercessory prayers, especially post mortem masses. This belief was still strong in eighteenth-century Catholic Europe. Italy, Spain and south-west Germany all exhibited such religious ‘frenzy’. Only France may be cited as an example to the contrary. Michel Vovelle has successfully proved that in Provence the will became simply a legal act distributing fortunes, with no reference to the pious clauses. However, we cannot extend this thesis, as Philippe Aries has mistakenly done, to the entire Catholic West.